The Influence Of Current Ratio, Return On Asset And Debt To Equity Ratio On Stock Prices With Dividen Policy As A Variable Intervening In The Company Registered Manufactures On BEI 2017-2021 - Wardana, Yusri; Arief, Muhammad; Suryani, Yani (Cattleya Darmaya Fortuna, 2024)
This research was conducted with the aim of determining the effect of Current Ratio, Return On Assets and Debt to Equity Ratio on stock prices with dividend policy as an intervening variable. This type of research is quantitative research. The population in this research is a manufacturing company listed on the Indonesia Stock Exchange (BEI) in 2017-2021. The sampling technique used purpose sampling with a sample of 27 companies in 5 consecutive years of observation. so the total observation data is 135 data. The data analysis technique for this research uses path analysis. The results of this research show that the current ratio, return on assets and debt to equity ratio have no direct effect on dividend policy. The current ratio and debt to equity ratio have a direct effect on share prices. Return on assets and dividend policy do not have a significant effect on share prices. Based on the results of statistical tests, it shows that the current ratio, return on assets and debt to equity ratio simultaneously influence stock prices. Dividend policy cannot mediate the relationship between the current ratio and share prices in manufacturing companies listed on the Indonesian Stock Exchange in 2017-2021.